Implementación de un sistema de información web para el control de ventas en la empresa VEREDAL R.S.M. PERÚ S.A.C. - Reátegui Ramírez, Francis Ivan (2014)
The following research report, "IMPLEMENTATION OF A WEB INFORMATION SYSTEM FOR SALE CONTROL IN VERDAL COMPANY RSM PERU S.A.C "; has the general objective of implementing a web information system to improve sale control in the company VERDAL RSM PERU SAC. Also as specific objectives; to evaluate the current situation of sales in the VERDAL COMPANY RSM PERU SAC, implement a web information system, and determine the impact of web information system to control sales. For the development of the research different methodologies were used. For information gathering techniques of observation, interviews were conducted, as well as review and assessment documents; for the analysis and design object-oriented methodology considering UML diagrams, the Unified Process and prototyping and PHP programming language used by the transmission PostgreSQL database and XAMMP Server package was used; each of these tools were taken in order to meet expectations for improving sales processes. Given the need to improve sales control, and hence greater efficiency in computer processes; This study will evaluate how to improve sales control by implementing a system of web information.